A bifunctional endolytic alginate lyase with two different lyase catalytic domains from Vibrio sp. H204 - Peng, Chune; Wang, Qingbin; Xu, Wei; Wang, Xinkun; Zheng, Qianqian; Liang, Xiaohui; Dong, Xiaodan; Li, Fuchuan; Peng, Lizeng (Frontiers in Microbiology, 2024)
Alginate lyases can fully degrade alginate into various size-defined unsaturated oligosaccharide products by β-elimination. Here, we identified the bifunctional endolytic alginate lyase Aly35 from the marine bacterium Vibrio sp. Strain H204. The enzyme Aly35 is classified into the polysaccharide lyase 7 superfamily and contains two alginate lyase catalytic domains. The relationship and function of the two lyase domains are not well known. Thus, the full-length recombinant enzyme and its truncated proteins Aly35-CD1 (catalytic domain 1), Aly35-CD2 (catalytic domain 2 domain) were constructed. The three enzymes showed similar biochemical characteristics and exhibited temperature and pH stability. Further research showed that Aly35 and Aly35-CD2 can efficiently degrade alginate, polymannuronate (PM) and polyguluronate (PG) into a series of unsaturated oligosaccharides, while Aly35-CD1 exhibits greater PM-degrading activity than that of Aly35-CD2 but can not degraded PG efficiently. The results suggest that the domain (Trp295-His582) is critical for PG-degrading activity, the domain has (Leu53-Lys286) higher PM-degrading activity, both catalytic domains together confer increased alginate (including M-blocks and G blocks)-degrading activity. The enzyme Aly35 and its truncations Aly35-CD1 and Aly35-CD2 will be useful tools for structural analyses and for preparing bioactive oligosaccharides, especially Aly35-CD1 can be used to prepare G unit–rich oligosaccharides from alginate.